1.60 Autoantibodies to human citrullinated fibrinogen (AhFibA) and their subfamilies directed to the fibrin peptides α36-50Cit38, 42 and β60-7460, 72, 74 are prognostic markers of radiographic damage in the very early arthritides of the French ESPOIR cohort. (31st January 2014) - Cornillet, M; Ruyssen-Witrand, A; Constantin, A; Meyer, O; Cantagrel, A; Serre, G; Nogueira, L; Nogueira, L; Nogueira, L
Abstract : Background and Objective: In established RA, autoantibodies (AAB) to human citrullinated fibrinogen (AhFibA) were demonstrated to be mainly composed of two subfamilies of AAB directed to immunodominant epitopes borne by the fibrin peptides α36-50Cit38, 42 and β60-74Cit60, 72, 74, respectively. Serum reactivity toward those peptides defines subgroups of patients. In the present study, we investigated whether AhFibA, anti-α36-50Cit38, 42 and β60-74Cit60, 72, 74 AAB, have different predictive values for disease outcome in very early RA. We also analysed whether these AAB differentially associate with SE and tobacco exposure. Materials and Methods: The French ESPOIR cohort is comprised of very early RA and of undifferentiated arthritides (UA) of less than 6-month duration. AhFibA, anti-α36-50Cit38, 42 and anti-β60-74Cit60, 72, 74 AAB were assayed by ELISA at baseline. After 3-year follow up, 701 patients were diagnosed RA according to the ACR/EULAR 2010 criteria. Relationships between SE HLA-DR alleles, tobacco exposure and the 3 AAB were analysed on those patients. Disease activity (DAS28, HAQ) and radiographic damage (SHS) were evaluated at baseline, and after 2- or 3-year follow up. Associations with clinical parameters and predictive value of each AAB were investigated. Results: AhFibA, anti-α36-50Cit38, 42 and anti-β60-74Cit60, 72, 74 AAB were detected in 349/701 (50%), 203/701 (29%), and 257/701 (37%), RA sera, respectively. Their positive predictive values for RA (72%, 82%, and 79%, respectively) were not significantly different. The presence and titre of each AAB were associated with SE HLA-DR alleles without significant additional effect of tobacco exposure. When 2 vs 0 copies of SE alleles were present, the odds ratios for AhFibA, anti-α36-50Cit38, 42 and anti-β60-74Cit60, 72, 74 AAB presence reached 8.0, 6.1 and 9.5, respectively. Neither the presence nor the titres of AhFibA, α36-50Cit38, 42 and β60-74Cit60, 72, 74 AAB were associated with DAS28 or HAQ at baseline and after 2 years. However, for the 3 AAB, patients whose sera contained one or several AAB had a progression of SHS during the first 3 years (medians from 6 to 8 depending on the subgroup), significantly higher than the AhFibA-negative patients (median = 4). Nevertheless, no significant correlation was observed between the titres of AAB and radiographic progression. Conclusion: Not only AhFibA but also their anti-α36-50Cit38, 42 and anti-β60-74Cit60, 72, 74 AAB subfamilies, are prognostic markers for bone erosion in RA. Moreover, AhFibA, anti-α36-50Cit38, 42 and anti-β60-74Cit60, 72, 74 AAB are similarly associated to HLA-DR and to tobacco exposure.